2007
DOI: 10.1080/10242420701568575
|View full text |Cite
|
Sign up to set email alerts
|

Cross-linked stem bromelain: A more stabilized active preparation

Abstract: Cross-linking of the protease stem bromelain (bromelain) with 0.25 and 1.25% glutaraldehyde (GTA) results in the formation of a large molecular mass, multimeric and soluble aggregate having comparable activity to the unmodified bromelain. Both 0.25 and 1.25% GTA cross-linked (CL) bromelain preparations were more stable against urea, guanidine hydrochloride (GdnHCl) and temperature-induced inactivation, and exhibited slightly better storage stability compared to the unmodified protease. Such a high molecular we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Anwar et al showed that bromelain gradually loses its activity after 3 h of incubation at 60°C, pH 7.0, with 18% of the original activity remaining after this period. When the temperature was increased from 50 to 60°C, bromelain activity was found to be 1.6 times lower.…”
Section: Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Anwar et al showed that bromelain gradually loses its activity after 3 h of incubation at 60°C, pH 7.0, with 18% of the original activity remaining after this period. When the temperature was increased from 50 to 60°C, bromelain activity was found to be 1.6 times lower.…”
Section: Stabilitymentioning
confidence: 99%
“…Therefore, it may be concluded that the molten globule state intermediate is essential for the denaturation of bromelain. 21 Anwar et al 22 showed that bromelain gradually loses its activity after 3 h of incubation at 608C, pH 7.0, with 18% of the original activity remaining after this period. When the temperature was increased from 50 to 608C, bromelain activity was found to be 1.6 times lower.…”
Section: Stabilitymentioning
confidence: 99%
“…Currently, a number of different enzyme immobilization techniques are being used in industry such as enzyme adsorption, entrapment, and cross-linking (Sheldon, 2007). A particularly attractive method is attachment/adsorption of the enzyme to the surface of a carrier which commonly results in enhanced enzyme stability Anwar et al, 2007;López-Gallego et al, 2005;Mozhaev et al, 1990;Qiu et al, 2005;Rocchietti et al, 2004). Stability enhancements have been shown after attachment to many different carriers, examples are magnetic beads (Qiu et al, 2005), mesoporous sol-gel glass (Wang et al, 2001), silica nanospheres (Wang and Caruso, 2004), Sepabeads (Rocchietti et al, 2004), agarose (Rocchietti et al, 2004), and protein-coated microcrystals (Kreiner and Parker, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…According to Anwar;Younus (2007), bromelain gradually lost its activity after 3h at 60 ºC, pH 7.0, and the remaining activity after incubation was 18%. That means, with the increase in temperature from 50 ºC to 60 ºC, bromelain lose 1.6-fold activity; since in our study, the remaining activity was around 29% at 50 ºC, pH 7.0, after 3 h incubation.…”
Section: Resultsmentioning
confidence: 99%